Mapping the landscape of Makerspaces in higher education: an inventory of research findings - Pallaris, Georgios; Zaphiris, Panayiotis; Parmaxi, Antigoni (My University, 2022)
Purpose: The purpose of this study is to chart the development of Makerspaces in higher education (MIHE), by building a map of existing research work in the field. Based on a corpus of 183 manuscripts, published between January 2014 and April 2021, it sets out to describe the range of topics covered under the umbrella of MIHE and provide a holistic view of the field. Design/methodology/approach: The approach adopted in this research includes development of the 2014-2021 MIHE corpus; literature overview and initial coding scheme development; refinement of the initial coding scheme with the help of a focus group and construction of the MIHE map version 1.0; refinement of the MIHE map version 1.0 following a systematic approach of content analysis and development of the MIHE map version 2.0; evaluation of the proposed structure and inclusiveness of all categories in the MIHE map version 2.0 using card-sorting technique; and, finally, development of the MIHE map version 3.0. Findings: The research trends in the categories of the MIHE map are discussed, as well as possible future directions in the field. Originality/value: This paper provides a holistic view of the field of MIHE guiding both junior MIHE researchers to place themselves in the field, and policymakers and decision-makers who attempt to evaluate the current and future scholar activity in the field. Finally, it caters for more experienced researchers to focus on certain underinvestigated domains.
Keywords: Higher education; Learning; Learning methods; Makerspaces